P033 Dendritic cells from patients with active IBD imprint pro-inflammatory α4β7+CLA+ T cells with potential for gut and skin homing. (27th May 2021) - Gordon, H; Rodger, B; Hoti, I; Lindsay, J O; Stagg, A
Abstract: Background: T cell trafficking contributes to inflammation and is a therapeutic target in IBD. Exposure of T cells to retinoic acid during activation induces expression of the gut trafficking integrin α4β7 and suppresses expression of cutaneous leukocyte antigen (CLA) which is required for entry into the skin. Although α4β7+ (gut homing) and CLA+ (skin homing) T cells are generally non-overlapping populations, we have recently observed a low frequency of α4β7+CLA+ (dual tropic) T cells in human blood; these cells may provide an immunological link between gut and skin. Here we investigate the generation of these population by DC in vitro, analyse the function of cells with different tissue tropism and examine the impact of intestinal and skin inflammation. Methods: Using flow cytometry, expression of α4β7 and CLA was assessed in whole blood, gut tissues, and on proliferating cells generated by stimulation of naïve CD4+ T cells with monoclonal antibodies (anti-CD3/28/2), or with allogeneic colonic or monocyte-derived DC (moDC). Production of TNFα and IFNγ was measured by intracellular cytokine staining. Results: α4β7+CLA+ T cells were found at low frequency in ileal lamina propria tissue as well as peripheral blood. Naïve CD4 T cells activated in vitro with antibodies expressed α4β7 but not CLA. In contrast, activation with DC resulted in the expression of both α4β7 and CLA and generated a dual tropic a4b7+CLA+ population. Colonic DC generated significantly more α4β7+ cells (p<0.05) and higher levels of α4β7 (p<0.05) than did moDC; colonic DC generated significantly fewer CLA+ cells (p<0.01). Nonetheless, a similar frequency of dual tropic cells was generated by both types of DC. moDC from healthy controls and patients with active IBD or skin inflammation all generated dual tropic cells. moDC from patients with active IBD, but not from patients with active inflammatory skin disease generated more gut tropic (α4β7+) T cells (p<0.05) compared with moDC from healthy controls. Following activation with moDC, cytokine production varied with homing profile. The frequency of TNFα+ and IFNg+ cells was significantly greater in CLA+ expressing populations (p<0.05 and p<0.01, respectively). Conclusion: CLA expression is induced by gut DC even though they potently upregulate α4β7. The dual tropic population generated is enriched for cells that produce inflammatory cytokines and it may provide a link between gut and skin inflammation. Monocyte-derived cells may contribute to the imprinting of T cell homing to the intestine and upregulation of this activity, specifically in active IBD, supports the concept that intestinal inflammation reprogrammes circulating monocytes.